If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 6v Solving 12 = 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 12 + -6v = 6v + -6v Combine like terms: 6v + -6v = 0 12 + -6v = 0 Add '-12' to each side of the equation. 12 + -12 + -6v = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -6v = 0 + -12 -6v = 0 + -12 Combine like terms: 0 + -12 = -12 -6v = -12 Divide each side by '-6'. v = 2 Simplifying v = 2
| 13y-2=17y+22 | | 2x+4=7yslope | | 0.18y+0.03(y+6000)=1440 | | 32-10x+x^2=y | | 3x+3.5y=5x+3.5y | | 4.9+5.7b-0.3(10b-7)=34 | | 11.97+x-.11=5x | | y=6x^2-24x+14 | | -4y-14=-6 | | M/4=2.7 | | (5*3)*(10*2)=x*0.6 | | -4x+-4x+6=6 | | 9p^2-18p-3=-10 | | 23-2(13-y)+10=48 | | 21-5x=17-2x | | 9-3p=36 | | t/3=1.36 | | (9k/65)=(1261/845) | | 100=8000/12(r) | | 208.0/13 | | t+2=12.25 | | p^2-65p+784=0 | | 7x+1.5y=3x+3.5y | | 100=16x+x-7x | | 5x-6=-96 | | 42+5(14+y)-10=108 | | -12+2y=10x | | -12x+2y=10x | | =-3x^2+8x+9 | | 15+9x=96 | | 5(4p-1)= | | 3x+7y=-35 |